Determining adrenocortical activity as a measure of stress in African elephants (Loxodonta africana) in relation to human activities in Serengeti ecosystem. (29th January 2013) - Tingvold, Heidi G.; Fyumagwa, Robert; Bech, Claus; Baardsen, Lisa F.; Rosenlund, Håvard; Røskaft, Eivin
Abstract: African elephants ( Loxodonta africana ) play a vital role in most African ecosystems, with their opportunity to alter the entire ecosystem by their sheer numbers. Defining and measuring animal welfare has been much discussed. One potential way of determining an animal's welfare is to record the absence or presence of stress. Little research on elephant welfare has so far been performed in the Serengeti ecosystem. The aim of this study was to record the faecal glucocorticoid metabolite levels of African elephants in areas with high or with minimum human interference. A total of 117 faecal samples were collected from randomly located single elephants as well as family herds in the northern, central and western Serengeti National Park (SNP) as well as in Grumeti Game Reserve and Ikoma Open Area, northern Tanzania in 2010. Elephants had higher levels of faecal glucocorticoid metabolites in the areas outside, compared with areas inside SNP. No single males were observed outside SNP, and in general, higher abundance of elephants was observed inside SNP. This suggests that elephants may prefer to reside in the potential safer areas inside the national park, demonstrating the importance of protected areas to improve the welfare of elephants.